India as a partner of German foreign policy - Christian Wagner (Stiftung Wissenschaft und Politik (SWP), 2024)
In recent years, the Indian Union has experienced a significant rise in status in German and European foreign policy. This process has been fuelled by India's economic dynamism as the fastest-growing democracy and its geopolitical role as a partner in the Indo-Pacific against China's hegemonic ambitions. For Germany, India is an indispensable but difficult partner. The country will maintain its strategic autonomy and use the Sino-American rivalry to further its own geopolitical ambitions. Despite the shared commitment to a rules-based international order, there will continue to be differences in the assessment of geopolitical conflicts, as in the case of Russia's war against Ukraine. The agreements on triangular cooperation and on migration and mobility have taken Indo-German relations to a new level. The first joint military exercises in the summer of 2024, which fulfilled India's long-held wish for closer defence cooperation, will help to further deepen bilateral relations. As India is becoming increasingly important in German foreign policy, it is necessary to significantly improve expertise on the country's domestic and foreign policy developments in the German academic landscape.
Keywords: 320; Indian Union; Germany; strategic autonomy; Sino-American rivalry; geopolitical ambitions; geopolitical conflicts; Russia's war against Ukraine; Indo-German Migration and Mobility Partnership Agreement; EU-India Free Trade Agreement; global agricultural power; defence cooperation; cyberdiplomatic cooperation